Review of Batteries Thermal Problems and Thermal Management Systems - Sökmen, K. Furkan; Çavuş, Muhammed (Bursa Teknik Üniversitesi, 2017)
Electric vehicles, lithium-based batteries that are used in solar energy storage are known from these products. Especially, in electric (EV), hybrid (HEV) and fuel cell vehicles (FCEV), battery technology has been an important contributor to reducing toxic gas emissions and using energy efficiently. In this study, we have examined some of the problems with associated solutions for battery heat management and what information is needed for proper design of battery heat management. Later we have examined the types of batteries which are used in electric vehicles and the characteristics of these batteries. We have mentioned about battery thermal management varieties such as air cooling, liquid cooling, phase change material (PCM), thermoelectric module and heat pipe. Finally, we have provided information on the shape of the battery pack and the thermal management effect of the battery packing.